Public injecting among a cohort of injecting drug users in Vancouver, Canada. Issue 1 (15th July 2008) - DeBeck, K; Small, W; Wood, E; Li, K; Montaner, J; Kerr, T
Abstract : Background: Despite the implementation of policy interventions to address open drug consumption, public injecting continues to occur in many urban settings. This study sought to examine public injecting among a community-recruited cohort of injecting drug users (IDUs) in Vancouver. Methods: The prevalence and correlates of recent public injecting among participants enrolled in the Vancouver Injection Drug User Study during the period of 1 December 2003 to 30 November 2005 were examined prospectively using generalised estimating equations (GEEs). Results: Among the sample of 620 active IDUs, at some point during the study period, 142 (22.9%) individuals reported "usually" or "always" injecting in public in the 6 months prior to their study visit. Factors that were significant and positively associated with recent frequent public injecting in multivariate GEE analysis include homelessness (adjusted OR (AOR) 6.70); frequent crack use (AOR 1.48); and frequent heroin injection (AOR 1.56). Recent frequent public injecting was found to be negatively associated with cooking and filtering drugs prior to injecting (AOR 0.50) and older age (AOR 0.95). Conclusion: The findings indicate that a substantial proportion of local IDUs frequently inject in public, and those who report recently injecting in public spaces appear to be a vulnerable population facing significant health hazards. The provision of secure housing may have the potential to protect the health of IDUs in this setting and significantly decrease the prevalence of public injecting. In addition, the findings support previous work suggesting that removing barriers to the use of Vancouver's existing supervised injection site may serve to further reduce public drug use.